Frederic William Maitland – Trust and Corporation - Getzler, J (TC Beirne School of Law, University of Queensland, 2016)
Maitland’s achievement in ‘Trust and Corporation’ is very gear; he explains with great clarity the difficult history and jurisprudence of trusts law in a radically short compass, and then investigates theories of legal personality, suggesting how the institutions of private associational law fits into a wider scape of political and social evolution.